NARRATIVE REVIEW: METODE ANALISIS PRODUK VAKSIN YANG AMAN DAN HALAL BERDASARKAN PERSPEKTIF BIOTEKNOLOGI - Fitri Rahmi Fadhilah; Firman Rezaldi; M Fariz Fadillah; Muhammad Faizal Fathurohim; Usman Setiawan (International Journal Mathla’ul Anwar of Halal Issues, 2021)
Biotechnology is the application of the branch of biology that involves other applied sciences in applying the principles of living things to produce goods and services, both conventional and modern. The application of biotechnological methods that are increasingly rapid, especially in the health and pharmaceutical fields, has a lot to fight for, especially in developing vaccines with healthy and halal criteria according to the biotech perspective. Halal status in the world of modern science has become a global issue, including the use of peptide-based vaccines. The results of the review show that a healthy and halal vaccine certainly has criteria, namely that it is safe to use, does not produce allergic reactions in the human body such as those made from horses or pigs. PCR is one of the molecular biology methods in the study of modern biotechnological methods which has a high level of sensitivity in detecting the content of pig DNA in various products, both medicinal and food.